A Case Report on the Effect of Veeratharadi Gana in the Management of Purple Urine Bag Syndrome (AYUSHDHARA, 2025)
Purple urine bag syndrome is a benign harmless condition with higher prevalence among individuals with long term indwelling Foleys catheter. In addition to extended catheter use and institutionalization, other risk factors include being female, having alkaline urine, and suffering from chronic constipation. This syndrome is also linked to urinary tract infections caused by bacteria that produce enzymes like sulphatase and phosphatase, which break down tryptophan. The resulting metabolites, indigo (blue) and indirubin (red), combine to create a purple colour, which is the characteristic feature of this condition. Veeratharadi gana mentioned in Susrutha samhitha is indicated in urinary disorders like Ashmari, Sarkara, Mutrakrichra, and Mutraghata. This case study deals with the case of a 28 years old male patient, with paraplegia following a fall from height, having loss of sensation below the umbilical region and catheterised, who had Purple Urine Bag Syndrome associated with urinary tract infection and was treated with Veeratharadi gana Kashaya as Pana (medicated drink). Following the administration of treatment, the urinary tract infection subsided, and the purple discoloration of the urine bag resolved, thereby demonstrating the efficacy of Ayurvedic medicine in the management of Purple Urine Bag Syndrome.